Teaching Reading by Using Cooperative Integrated Reading and Composition - Irwan Doni; Zulfadli A. Aziz; Siti Sarah Fitriani (English Education Journal, 2018)
This experimental study was done with the third-semester, Grade 11, Accounting students at SMKN 3 in Lhokseumawe to investigate differences in reading comprehension learning ability between students who were taught reading, using the Cooperative Integrated Reading and Writing Techniques (CIRC) and those who were taught using the Grammar Translation Method. This study also aimed to find out the students’ perceptions toward the use of the CIRC technique for teaching-learning reading comprehension. Two classes were selected as the research sample, an experimental class (EG) and a control class (CG). Each class had 22 students so the total sample was 44 students. The research data was obtained through tests  (i.e. a pre-test and a post-test) and a questionnaire with the EG. SPSS version 17 was used to analyze the data. The results showed that the mean score of the EG in the post-test at 81 was significantly higher than that of the CG at 72. The value of  significance for the EG and the CG in the post-test was 0.031, lower than α = 0.05. Hence Ha was accepted, indicating that there was a significant difference in reading comprehension ability between the students taught by using the CIRC technique and those taught by using the Grammar Translation Method. Therefore, it can be concluded that teaching reading comprehension using the CIRC technique is more effective than by using the Grammar Translation Method.